Predictors of white matter hyperintensities in the elderly Congolese population - Yohe, Emile Omba; Alonso, Alvaro; Drane, Daniel L.; Patel, Saranya Sundaram; Schwinne, Megan; Epenge, Emmanuel; Gikelekele, Guy; Herve, Esambo; Kavugho, Immaculee; Tshengele, Nathan; Mampunza, Samuel; Mananga, Lelo; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionWhite matter hyperintensities (WMHs) are strongly linked to cardiovascular risk factors and other health conditions such as Alzheimer’s disease. However, there is a dearth of research on this topic in low-income countries and underserved populations, especially in the Democratic Republic of Congo (DRC) where the population is aging rapidly with increasing cardiovascular risk factors and dementia-related diseases. This study evaluates health factors associated with WMH in the elderly Sub-Saharan Africa (SSA), specifically Congolese adults.MethodsIn a cross-sectional study of 77 people from the DRC, participants underwent neuroimaging to analyze WMHs volume and completed clinical evaluation, laboratory-based blood exams, self-reported questionnaires, and interviews. A simple linear regression model was conducted to test the association between WMHs and potential predictors (dementia, age, sex, hypertension, diabetes, tobacco abuse, stroke, high cholesterol, cardiovascular medication, and alcohol abuse). Stepwise selection and backward elimination analyses were performed to obtain the final model. Finally, a multiple linear regression model was conducted to assess the association between WMHs and variables retained in the final model (dementia, sex, and age).ResultsOf the 77 individuals, 47 (61%) had dementia, 40 (52.6%) were males, and the mean age was 73 years (± 8.0 years standard deviation). In simple linear regression models, WMHs was significantly associated with dementia (expβ1 = 1.75, 95% CI = 1.14–2.71, p-value = 0.01) though it had a weak association with age (expβ1 = 1.03, 95% CI = 1.00–1.05, p-value = 0.05) and sex (male) (expβ1 = 0.66, 95% CI = 0.43–1.01, p-value = 0.05). In multiple linear regression models, WMHs was statistically significantly associated with dementia (expβ1 = 1.97, 95% CI = 1.31–2.95, p-value =0.001), male sex (expβ2 = 0.54, 95% CI = 0.36–0.80, p-value = 0.003), and age (expβ3 = 1.03, 95% CI = 1.00–1.06, p-value = 0.03). However, WMHs was not significantly associated with common cardiovascular risk factors, such as high blood pressure, diabetes, tobacco use, obesity, and high cholesterol levels.DiscussionWMHs is significantly associated with dementia, sex, and age in the Congolese population. Understanding these predictors may improve our ability to diagnose, assess, and develop preventative treatments for white matter disease in SSA/DRC populations, where neuroimaging is difficult to obtain.